Medical physical culture in the physical rehabilitation of children with congenital heart diseases in the preoperational period - Дугіна [Dugina L.], Ліліана В'ячеславівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--> the question of congenital heart diseases is considered for children, statistical data of morbidity and classification of congenital heart diseases are presented. Description of bodily condition of children is considered with this pathology. Substantive methodical provisions are described to application of facilities of medical physical culture at operative treatment of children on adaptation and preparatory the stages of the preoperational period rehabilitations which promote efficiency of holiatry. The methods of teaching to respiratory exercises are presented for the children of junior and senior age. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->